2016
DOI: 10.1007/978-3-319-43589-3_12
|View full text |Cite
|
Sign up to set email alerts
|

AMPK in Pathogens

Abstract: During host-pathogen interactions, a complex web of events is crucial for the outcome of infection. Pathogen recognition triggers powerful cellular signaling events that is translated into the induction and maintenance of innate and adaptive host immunity against infection. In opposition, pathogens employ active mechanisms to manipulate host cell regulatory pathways toward their proliferation and survival. Among these, subversion of host cell energy metabolism by pathogens is currently recognized to play an im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 183 publications
(183 reference statements)
0
9
0
Order By: Relevance
“…AMPK functions as a modulator of host defenses against intracellular bacterial, viral, and parasitic infections [ 9 , 10 , 11 , 12 ]. Indeed, numerous viruses have the ability to trigger metabolic changes, thereby modulating AMPK activity and substrate selection [ 13 ], and AMPK signaling could facilitate or inhibit intracellular viral replication depending on the virus infection [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…AMPK functions as a modulator of host defenses against intracellular bacterial, viral, and parasitic infections [ 9 , 10 , 11 , 12 ]. Indeed, numerous viruses have the ability to trigger metabolic changes, thereby modulating AMPK activity and substrate selection [ 13 ], and AMPK signaling could facilitate or inhibit intracellular viral replication depending on the virus infection [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Adenosine 5′-monophosphate-activated protein kinase has been extensively studied as a pivotal regulator of cellular energy metabolism ( 47 ). Recent studies have revealed that AMPK was involved in the regulation of virus replication ( 18 ). Inhibition of AMPK severely attenuated HCMV replication, suggesting that AMPK was required for HCMV replication ( 48 , 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…Adenosine 5′-monophosphate-activated protein kinase (AMPK) is a heterotrimeric serine/threonine kinase ( 17 ), which is considered as pivotal regulator of host cellular metabolism via sensing cellular energy status ( 18 ). When the energy levels in cells decrease, AMPK is activated through phosphorylation by an upstream kinase ( 18 ). Activated AMPK thereby downregulates anabolic processes that consume ATP and upregulates catabolic processes that synthesize ATP ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is most likely that T. cruzi profits from the stress generated from ROS, and this might provide an adaptive evolutionary advantage for the parasite. Many evidences point towards that direction: parasites can proliferate in response to H 2 O 2 [ 47 ] and the increased growth of epimastigotes in response to H 2 O 2 involves a calmodulin-dependent protein kinase II CAMKII-like enzyme in the proliferation pathway and a cascade of events including AMP kinase in the host [ 38 , 56 , 57 ] and also the mitochondrial ROS produced into the mitochondria, which results from heme metabolism and enhances the parasite growth [ 49 ]. As mentioned earlier, heme also controls the activity of TcK2 and in turn the process of translation in the parasite.…”
Section: Introductionmentioning
confidence: 99%